1998
DOI: 10.1007/bf03175429
|View full text |Cite
|
Sign up to set email alerts
|

Where's the reef: The role of framework in the Holocene

Abstract: Holocenereef models generallyemphasizethe role of in-placeandinterlocking framework in the creationof a rigid structure thatrises aboveits surroundings. By extension, a numberof ancientbiohermaldepositshave been disqualifiedas "true reefs" owing to their lack of recognizable framework, Fifty-four cores from several eastern Caribbean sites ( Fig. 1) clearly demonstrate that in-place and interlocking frameworkis notconunon in thesereefs thatarecomprisedof varyingmixturesof recognizablecoral (primaryframewerkj.Io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 8 publications
0
32
0
Order By: Relevance
“…In contrast, Hubbard et al (1986Hubbard et al ( , 1998 suggested an incremental accumulation with alternating episodes of sedimentation and coral colonization. Pauses in growth are interpreted as reflecting changes in conditions, in nutrient supply and in temporary "drowning" of the substrate or spatial variability.…”
Section: Bioconstruction and Reef Accumulationmentioning
confidence: 83%
See 1 more Smart Citation
“…In contrast, Hubbard et al (1986Hubbard et al ( , 1998 suggested an incremental accumulation with alternating episodes of sedimentation and coral colonization. Pauses in growth are interpreted as reflecting changes in conditions, in nutrient supply and in temporary "drowning" of the substrate or spatial variability.…”
Section: Bioconstruction and Reef Accumulationmentioning
confidence: 83%
“…It may be impossible to differentiate algally encrusted in place coral from encrusted coral debris, given the narrow perspective afforded by cores. In an important reappraisal, Hubbard et al (1998) suggested, on the basis of 74 cores in contrasting areas in the Caribbean, that corals comprise less than 30% of Holocene reef interiors, and that less than half of this volume is "in place". Many shallow holes have been drilled, but with varying success.…”
Section: Introductionmentioning
confidence: 98%
“…Carbonate sediments make up the majority of CaCO 3 stored on coral reefs and are important to the development of reef structures by lithification and by acting as infilling of reef framework (Hubbard et al 1998;Eyre et al 2014). These reef structures provide important habitats for a large number of species and alleviate potentially destructive wave energy and coastal erosion.…”
Section: Significance For Natural Systems and The Potential Consequenmentioning
confidence: 99%
“…Less readily apparent is the fact that the interiors of many (or possibly most?) of these structures contain less than 30% recognizable coral, with only a portion of that in place (Conand et al, 1997;Hubbard et al, 1998). The remainder is sand and rubble caused by ubiquitous bioerosion plus void space.…”
Section: Introductionmentioning
confidence: 99%